Education and Personality Development in Information and Communication Activities - A. V. Gagarin; L. K. Raitskaya (Vestnik MGIMO-Universiteta)
The article considers the scope for the shift to personality-oriented paradigm through the personal inclusion into specially organized information and communication activities in the Internet environment; the authors also give the essence, specific features and functions of those activities.